Faculty of Nursing at Universidad de Antioquia: 70 years, a whole lifetime caring for lives - Zuleta Vanegas, Lina María; Lopera Arrubla, Claudia Patricia (Investigación y Educación en Enfermería, 2020)
Seventy years have passed since Doctor Ignacio Vélez Escobar, in his possession speech as dean of the Faculty of Medicine at Universidad de Antioquia, on 23 August 1950, had the initiative of creating a new school of nursing. Thus, on 29 September of that year, Resolution Number 30 by the Directive Council at Universidad de Antioquia approved opening the School of Nursing, as dependence ascribed to the Faculty of Medicine. It operated under this figure until August 1975 when its creation resolution was repealed and it was determined that it would continue operating as a teaching unit at Universidad de Antioquia, but conserving its figure of School, which it kept until May 1981 when the same Council approved the transformation from School into Faculty.